PERAN PERANGKAT DESA DALAM AKUNTABILITAS PENGELOLAN KEUANGAN DESA DI DESA LEBANI KECAMATAN MAIWA KABUPATEN ENREKANG: Indonesia - Zarina (Jurnal Akuntansi Kompetif, 2025)
This Reaarch aimend to study the role of Villange apparatus on Accountability for village financial management in Lebani Village, Maiwa Sub-distict, Enrekang Regency. The date were collected thorough questionnaire and documentation. The sample of this research was 14 people involved in accountabiliy for village financial management. The datw was analyzed usinf descripstive Quantitative Analysis. The Result of this research showed that the role of Village apparatus on accuntability for village financial management already had a role that can be seen in stages of pleanning, implementation, administrasi, reporting, and accountability in accordance with the domestic Government Regulation number 113 on 2014. Keywords : The role of Village Apparatus, Accountability for Village Financial Management